2008
DOI: 10.1108/13598540810860985
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of an integrated industrial supply chain

Abstract: PurposeThe purpose of this article is to investigate the impact of integrated supply chain management on productivity, efficiency, and performance of participants in the system, in an industrial setting in the USA.Design/methodology/approachThis study uses longitudinal and experiment field study. Actual organizational data from the survey firm was used. Follow‐up interviews were conduced with key managers in the manufacturing facility.FindingsThe results show positive and substantial improvements in overall pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…(), Barratt (), Fisher (), Selldin and Olhager (), Elmuti et al . (), Sun et al . () and Klibi and Martel () as some examples of the many in the literature.…”
Section: Reality – Ontological Levels and Assumptionsmentioning
confidence: 99%
“…(), Barratt (), Fisher (), Selldin and Olhager (), Elmuti et al . (), Sun et al . () and Klibi and Martel () as some examples of the many in the literature.…”
Section: Reality – Ontological Levels and Assumptionsmentioning
confidence: 99%
“…l Studies describing current practice, typically in the form of case studies (n = 43). 45,46,48,49,[52][53][54][55][56][57]59,60,67,69,70,72,73,78,83,[86][87][88][89][90]92,94,[96][97][98][99][100][101]103,105,106,[108][109][110][111][112][113][114][115] Primary studies were set mostly in the USA (n = 20), 48,[52][53][54]57,70,87,88,…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Identified studies covered a range of sectors and industries, including textiles, information technology (IT), 99 the automotive industry 45,46,68 and manufacturing. 57,63,65,71,76,77,79,80,86,102,104,113 We further identified 21 studies addressing the health-care sector specifically. 48,49,52,54,58,62,70,72,87,88,90,94,96,97,103,105,106,[108][109][110]115 Analysis of studies identified three overarching themes: organisational and strategic issues; collaboration and relationships (within an organisation and with suppliers); and materials management and information flows within an organisation.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This research project is a single case study of which the research methodology relies on multiple sources of evidence so as to add to the breadth and depth of data collection. Such single case studies can be seen in numerous research such as the one carried out in Northeastern United States of America on the subject of how a manufacturing plant perform in its integrated industrial supply chain (Elmuti et al, 2008). To assist in bringing forth richness of data together, triangulation would be carried out so as to contribute to the validity of the research (Yin, 2003).…”
Section: Methodsmentioning
confidence: 99%